Optimizing the kidney exchange problem with a budget for simultaneous crossmatch tests - Romanciuc, Valeria (2019)
Many people in the world suffer from end stage renal disease, which has transplantation as the most effective form of treatment. However, kidneys obtained from deceased donors are not nearly enough to meet demand and willing living donors may display incompatibilities with their intended recipient. Kidney Exchange Programs have emerged as an attempt to answer the transplant shortage and bypass these incompatibility issues between donor-patient pairs. The process of selecting the pairs participating in the transplantation plan requires optimization models, one of which is presented in the current paper. We focus on maximizing the expected number of transplants taking into account that only a given number of actual incompatibility (crossmatch) tests can be made. We present an integer programming model to address this problem when recourse is feasible and we compare computationally its outcomes with other two approaches in 150 instances.